Impacts of Land-Use Changes on Water Quality by an Application of GIS Analysis: a Case Study of Nerus River, Terengganu, Malaysia - Ekhwan Toriman, Mohd; Mohammed Ali Alssgeer, Hassan; Barzani Gasim, Muhammad; Amri Kamarudin, Khairul; Mohamed Daw, Mabroka; Omaer Mohammed Alabyad, Laila (International Journal of Engineering and Technology, 2018)
The impact of land use change on water quality of Nerus River Kuala Terengganu is an event that needs to be taken seriously in this study. The objectives of the study area are to carried out 13 parameters water quality samplings and analysis of Nerus River as well as to classify water quality concentration based on NWQS and WQI classifications; to interpret 2000 and 2013 land use/land cover maps of Nerus River Basin and to evaluate water quality data by statistical technique such as similarities and dissimilarities between sampling stations to determine pollution sources. Methods that were used in study area GIS will use to classify land cover/land use changes in the catchment between 2000 and 2013 land use maps. Water quality analysis and monitoring were done based on three sampling stations during both dry and wet seasons, involving analysis 13 water quality parameters. Water quality classification is using the National Water Quality Standard (NWQS) and the Water Quality Index (WQI). Statistical analysis such as similarities and dissimilarities between sampling stations was applied. Results of the study show that the river was classified as class II (slightly polluted), III (moderately polluted) in accordance with previous studies.Â Â